Copper phosphate compounds with visible-to-near-infrared-active photo-fenton-like photocatalytic properties - Han, Gill Sang; Cho, In Sun (Journal of the American Ceramic Society, 2020)
Copper pyro-, ortho-, and tetra-phosphate compounds (Cu2P2O7, Cu3P2O8, and Cu4P2O9) with the general composition, CuxP2O5+x (x = 2, 3, 4), were prepared through the conventional solid-state synthesis route, and their optical properties and visible-infrared light-induced photocatalytic activities were investigated for the first time. The copper phosphate compounds showed comparable particle sizes, and their primary optical bandgaps were estimated to lie in the range of 2.8-3.6 eV. Their photocatalytic activity was evaluated by the kinetics of decomposition of rhodamine B (RhB) solution under visible-light irradiation (>420 nm). Among the three kinds of copper phosphate, Cu4P2O9 exhibited the highest photocatalytic activity due to its smallest bandgap (of the three compounds considered) and appropriate band positions. More interestingly, the three copper phosphate compounds, particularly Cu3P2O8, show strong near-infrared (NIR) light absorption, thereby enabling the NIR-induced photocatalytic decomposition of RhB in the presence of hydrogen peroxide. Finally, a possible photo-Fenton photocatalytic reaction mechanism was also proposed based on the band structure/position.
Keywords: Near infrared light; Phosphate compounds; Photocatalytic decomposition; Photocatalytic property; Photocatalytic reactions; Solid-state synthesis; Visible infrared light; Visible-light irradiation; band structure; copper phosphates; Cu3P2O8; photo-Fenton-like photocatalyst; visible-to-near-infrared light absorption